Keanekaragaman serangga dan struktur vegetasi pada habitat burung insektivora Lanius schach Linn. di Tanjungsari, Yogyakarta - Fredy Lala; F. X. Wagiman; Nugroho S. Putra (Jurnal Entomologi Indonesia, 2013)
Insect diversity and vegetation structure are two aspects that affect the reproduction of insectivorous birds. The objective of this study was to investigate the characteristics of the original habitat Lanius schach in Tanjungsari of particularly the type, composition of vegetation, and preference to insect sprey. Observation of vegetation and insects were conduct using a combination methods of the track and checkered line on the transect along the 10 km (ten observation points). Insect and tree species were counted on plot (20 m x 20 m), shrub (10 m x 10 m), bush (5 m x 5 m), and grass (2 m x 2 m). Vegetation analysis was used to calculate the structure and composition of vegetation, whereas Shannon diversity index was used for insect diversity. Prey test was conducted to determine the preferences of insectivore birds on insects. The composition of the vegetation species consists of 7 grasses, 20 bushes, 5 shrubs and 18 trees. The dominant species of vegetation based on highest important value index was Tectona grandis, Ipomoea sp., I. cylindrica, and Panicum brevifolium respectively. The highest diversity index of vegetation group were bush (2.430), tree (1.696), grass (1,680), and shrubs (1.364), respectively. Insect diversity index was 2.572 and grasshoppers (Orthoptera) was the most preferred prey by L. schach. Overall, the habitat of insectivore birds L. schach are dominated by T. grandis, and has high diversity of bush.